Synthesis, Properties, and Selected Technical Applications of Magnesium Oxide Nanoparticles: A Review - Hornak, Jaroslav (International journal of molecular sciences, 2021)
In the last few decades, there has been a trend involving the use of nanoscale fillers in a variety of applications. Significant improvements have been achieved in the areas of their preparation and further applications (e.g., in industry, agriculture, and medicine). One of these promising materials is magnesium oxide (MgO), the unique properties of which make it a suitable candidate for use in a wide range of applications. Generally, MgO is a white, hygroscopic solid mineral, and its lattice consists of Mg2+ ions and O2- ions. Nanostructured MgO can be prepared through different chemical (bottom-up approach) or physical (top-down approach) routes. The required resultant properties (e.g., bandgap, crystallite size, and shape) can be achieved depending on the reaction conditions, basic starting materials, or their concentrations. In addition to its unique material properties, MgO is also potentially of interest due to its nontoxicity and environmental friendliness, which allow it to be widely used in medicine and biotechnological applications.
Keywords: electrotechnical applications; crystallite size; chemické modely; structural properties; bottom-up; dielectric properties; Magnesium Oxide; oxid hořečnatý; nanočástice; Adsorption; Models, Chemical; nanomaterials; magnesium oxide; synthesis; Nanoparticles; adsorpce